2022
DOI: 10.1002/pd.6239
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for a non‐invasive prenatal test as first‐line screening for Down Syndrome: A discrete choice experiment

Abstract: Objective To investigate preferences of pregnant women for the characteristics of prenatal testing, and to quantify their willingness‐to‐pay (WTP) for non‐invasive prenatal testing (NIPT) as first‐line screening for Down Syndrome. Method A cross‐sectional discrete choice experiment survey including five testing attributes was administered to 192 pregnant women (≤14 weeks' gestation) who were aged ≥21 years in Singapore. We calculated marginal WTP for improvements in testing characteristics and NIPT. Results We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In contrast, another study from Singapore focusing on willingness-to-pay (WTP) for NIPT revealed that while older, more educated women, or those intending to terminate a pregnancy if affected, showed a higher WTP for NIPT, the general population was not willing to pay extra for NIPT over standard testing as a first-line screening method. This highlights a discrepancy between perceived value and actual financial commitment to NIPT in different cultural and economic settings, underscoring the complex dynamics that influence prenatal testing decisions globally (34).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, another study from Singapore focusing on willingness-to-pay (WTP) for NIPT revealed that while older, more educated women, or those intending to terminate a pregnancy if affected, showed a higher WTP for NIPT, the general population was not willing to pay extra for NIPT over standard testing as a first-line screening method. This highlights a discrepancy between perceived value and actual financial commitment to NIPT in different cultural and economic settings, underscoring the complex dynamics that influence prenatal testing decisions globally (34).…”
Section: Discussionmentioning
confidence: 99%